Effect of Counseling Based on Gamble's Approach on Postpartum Anxiety in Primiparous Women - Zahra Hajjarian; Fatemeh Zahra Karimi; Seyed Reza Mazloom; Ziba Taghizdeh; Mohsen Asgharinekah (Mashhad University of Medical Sciences, 2021)
Background & aim: The postpartum period is a time of extreme vulnerability to various psychiatric disorders, such as anxiety, which exert profound negative impacts on the health of neonates, mothers, and families. Therefore, it is necessary to perform some interventions to prevent and mitigate postpartum anxiety. The current study investigated the effect of counseling based on Gamble's approach on postpartum anxiety in primiparous women. Methods: This randomized clinical trial was carried out on 60 primiparous women referred to Mashhad health centers in 2018. Participants in the intervention group received midwife-led individual counseling based on Gamble's approach during three prenatal and one postpartum session, apart from routine prenatal care. The control group only received routine prenatal care. A questionnaire to measure demographic and obstetric data as well as Depression, Anxiety and Stress Scale-21 (DASS-21) were used to collect data. The obtained data were analyzed in SPSS software (version 16) using Mann-Whitney, chi-square and independent t-test. Results: There was no significant statistical difference between the two groups before intervention (p <0.05). The mean and standard deviations of women's anxiety in the intervention and control groups were obtained as 7.5±1.1 and 8.6±2.4, respectively. The results of the Mann-Whitney test demonstrated that the level of anxiety in the intervention group was significantly lower, compared to that in the control group (P=0.008).   Conclusion: Counseling based on Gamble's approach reduced postpartum anxiety in primiparous women. Therefore, it can be used during pregnancy and postpartum period as an effective, simple, and adverse-effect-free method to reduce anxiety during the postpartum period.